The Behavior and Performance of Cashew Market in South Buton Regency, Indonesia - Wa Ode Al Zarliani; Wardana Wardana; Achmad Amiruddin (Caraka Tani: Journal of Sustainable Agriculture, 2021)
Some of the major problems in cashew marketing performance are low production, inefficient marketing system and low income received by farmers. In addition, farmer with a low bargaining position will only receive prices from market players in the midst of increasing demand and competition in the market. The aim of this study is to examine the behavior and performance of the cashew market in South Buton Regency, Indonesia. Furthermore, the marketing channels, margins, costs and benefits received by each agency were used to analyze the technical and economic efficiency. In addition, random and snowball sampling techniques were applied to determine the farmers and traders, respectively. The results showed that the behavior of market price was based on the cost analysis, supply and demand, as well as the expected benefit. Meanwhile, the transactions were made partially (initial payment before and after the products were sold) and some in cash. The market players were unique in providing cooperate capital to farmers. Moreover, the market performance shows an efficient system from the two channel patterns formed, close distance indicates a technically efficient system and low marketing cost indicates economic efficiency.